HIV point-of-care diagnostics: meeting the special needs of sub-Saharan Africa - Godwin Abazho Aleku; Moses P Adoga; Simon M Agwale (Journal of Infection in Developing Countries)
Sub-Saharan Africa, accounting for 70% of the 35 million people living with HIV worldwide, obviously carries the heaviest burden of the HIV epidemic. Moreover, the region’s poor health system occasioned by limited resources and inadequate skilled clinical personnel usually makes decentralization of HIV care difficult. Therefore, quality diagnostics that are easy to use, inexpensive, and amenable for use at point of care (POC) are a dire necessity. Clearly, such diagnostics will significantly lessen the pressure on the existing over-stretched centralized HIV laboratory services. Thankfully, some POC diagnostics are already being validated, while others are in the pipeline. As POC test kits emerge, implementation hurdles should be envisaged and planned for. This review examines emerging HIV diagnostic platforms, HIV POC product pipelines, gaps, perceived POC implementation challenges, and general recommendations for quality care.